Daily Vaginal Application of Dienogest (Visanne©) for 3 Months in Symptomatic Deeply Infiltrating Rectovaginal Endometriosis: A Possible New Treatment Approach? - Andreas D. Ebert (Hindawi Limited, 2018)
A 27-year-old patient suffering from deeply infiltrating rectovaginal endometriosis was treated with 2 mg/day dienogest vaginally for 3 months. The therapy was tolerated very well. The patient reported less side effects compared to the oral use of dienogest. After 3 months of dienogest treatment, the rectovaginal gynecological examination identified the visible vaginal part of endometriosis in remission. The firm endometriosis node approximately 3 cm in size and approximately 10 cm ab ano was still palpable, but it was much less painful. The laboratory values for luteinizing hormone (LH) and follicle-stimulating hormone (FSH) were unremarkable, with an LH/FSH quotient of 0.7 during dienogest treatment, while 17-β estradiol and progesterone were suppressed. At palpation and vaginal ultrasonography, there was no change in the findings before and after 3 months of dienogest treatment, but the patient was now de facto asymptomatic. To the best of our knowledge, this is the first report of a vaginal dienogest treatment in symptomatic deeply infiltrating rectovaginal endometriosis. Vaginal administration of dienogest should receive further investigation in pharmacokinetic and clinical studies.